The muppets - Segel, Jason, 1979-; Adams, Amy.; Cooper, Chris, 1951-; Jones, Rashida; Whitmire, Steve, 1959-; Jacobson, Eric.; Goelz, Dave.; Linz, Peter; Hoberman, David, 1953-; Lieberman, Todd.; Stoller, Nicholas; Bobin, James; et al. (Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2012)
While on vacation in Los Angeles, Walter and his friends, Gary and Mary, try to raise ten million dollars to save the Muppet Theater from Tex Richman, a business man who wants to demolish the theater in order to drill for oil.
Title and credits from container; additional cast from IMDb.
Originally produced as a motion picture in 2011.
Bonus features: blooper reel; hilarious deleted scenes; a cavalcade of unseen cameos; complete collection of the spoof trailers.
At head of title: Disney.
Director of photography, Don Burgess ; edited by Jason Thomas ; music supervisor, Bret McKenzie ; original score by Christophe Beck.
Jason Segel, Amy Adams, Chris Cooper, Rashida Jones ; Muppet performers: Steve Whitmire, Eric Jacobson, Dave Goelz, Bill Barretta, David Rudman, Matt Vogel; voice, Peter Linz.
Keywords: Muppets (Fictitious characters) -- Juvenile drama; Fund raising -- Juvenile drama; Los Angeles (Calif.) -- Juvenile drama; Puppet films; Feature films; Films for the hearing impaired; Video recordings for people with visual disabilities